Control of Oscillation Amplitude of Oscillating Motors - Brazaitis, A.; Guseinovienė, E.; Jankūnas, V. (Elektronika ir Elektrotechnika, 2010)
The problem of increasing of performance parameters and efficiency of oscillating motors with hyperbolical dependence of permeance is analyzed in this paper. For this purpose it is used sharp rise part of dependence of permeance on coordinate of pendulum λ(h) approaching pendulum to the stator at most. It was used positioning of oscillating amplitude regarding the stator with aim to avoid of impacts the pendulum to the stator when working conditions change. Method was certified by modeling. In process of drive modeling for realizing of this principle simple modern technical means were used: microcontroller for system control, motor’s voltage of controlled supply source must be rectangular pulses with const amplitude and controlled width of pulse, simple one bit sensor for feedback signal. Modeling results confirm that purpose can be achieved. Ill. 7, bibl. 8, tabl. 1 (in English; abstracts in English, Russian and Lithuanian).